Integrating Disaster Risk Reduction Education into Local Curricula in Nepal - Pahadi, Toya Nath; Budhathoki, Chitra Bahadur (HPE Forum, 2026)
While school safety in Nepal is compromised due to the vulnerability of multiple hazards, the incorporation of disaster risk reduction (DRR) education into local curricula remains limited and uneven. The document analysis method was adopted to review the thirty-two local curricula (2076-2080 B.S.) and explore the integration of DRR education into local curricula, examining variations over time, across regions, and grade levels, as well as by thematic domains, hazards incorporated, and the instructional weightage allocated to them. Among these curricula, two curricula have not incorporated DRR content at all, reflecting an implementation gap. The integration is led by Bagmati and Lumbini provinces, while Madhesh, Karnali, Koshi, and Gandaki provinces are lagging, highlighting regional disparities. Most of the DRR content is integrated with other thematic domains, and annual teaching hours vary widely (5- 40). Despite progress in integration, uneven coverage of hazards and poor attention to local risks indicate a policy-practice gap. Standardized benchmarks and alignment with hazard mapping are essential to effectively integrate the DRR education into local curricula in Nepal.